CP-174 Therapy education programme in heart failure – 3 year evaluation. (14th February 2016) - Kowal, C; Eliahou, L; Hauer, S; Salabert, C; Chaumais, MC
Abstract : Background: Cardiac insufficiency is a common, chronic, life threatening disease. Therapeutic patient education is a key component to prevent heart failure and sustain quality of life. In this context, a therapeutic educational programme was set up in 2009 by both the cardiology and pharmacy departments. The programme's outcomes were determined according to guidelines. Purpose: To assess the effectiveness of the therapeutic educational programme and patient satisfaction. Material and methods: Patient's knowledge assessment was carried out before (D0) and after education at 2 and 6 months (M2 and M6) according to 20 right/wrong questions. For each answer, the patient was asked to rate the degree of certainty. Self-reported skills and satisfaction were rated using an anonymous questionnaire just after the programme (D1) and during follow-up at M2 and M6. Results: Between January 2013 and October 2015, 110 patients were included. Among these, knowledge was assessed in 92 patients at D0. The rate of correct responses (CR) improved from 71% at D0 to 82% at M2. It was maintained at 81% at M6. A correlation was observed between CR improvement and degree of certainty. The percentage of CR with a degree of certainty of 100% increased by 15% and 16% at M2 and M6, respectively. Self-reported skills were focused on management of the disease, treatments and diet. 53 patients (48%) completed the survey. They considered that the programme (i) improved their understanding and management of the disease: 93% (D1), 94% (M2), 94% (M6); (ii) helped them make the best use of their treatment: 93% (D1), 93% (M2), 93% (M6); (iii) and facilitated dietary self management: 95% (D1), 98% (M2), 98% (M6). Patient satisfaction rate was elevated just after the programme at D1 (93%) and was maintained at M2 (95%) and M6 (94%). Conclusion: Analysis of 3 year data reported that this programme satisfied patients, and allowed them to acquire knowledge and skills in the management of their cardiac insufficiency. Patient follow-up after education is a critical issue in this programme to sustain skills and knowledge that patients have acquired about their disease. References and/or Acknowledgements: Brunie, et al . J Pharm Clin 2010;29:98-102 No conflict of interest.